Identification of multiple disease resistant maize accessions - M. SINGH, V.K. MALIK*, ROBIN GOGOI, K.S. HOODA and (Indian Phytopathology, 2017)
Maize (Zea mays L.; 2N=20) is an important cereal crops of the country and grown over an area of 8.67 million ha. Maize is grown in more than 150 countries and contributes a lot to nutritional food security of the society. Maydis leaf blight and Banded leaf and sheath blight diseases are the most important foliar diseases of kharif season causing immense losses in yield. Both the diseases are of high damaging potential, so large number of normal maize hybrids of different maturity groups along with specialty corn hybrids were screened against both the diseases during kharif 2014 under artificial inoculation conditions at Karnal and Delhi. In late maturity group, one hybrid namely DAS-MH-105 was observed as resistant to MLB and BLSB based on average of both the locations. Twelve hybrids including HM 8-C, DKC 9144 (IM8478), AQH 9 and Kuber Shakthi were recorded as moderately resistant for normal maize of medium maturity group. Seven and three hybrids exhibited moderately resistant reaction for early and extra early group, respectively. CMH 10-531of early maturity group was found moderately susceptible to both the diseases. In case of specialty corn hybrids including VEHQ 11-1 and HQPM1-C for quality protein maize; HPC 1 and BPC 3 for pop corn; ADVSW-1 and Bisco MaDHAU for sweet corn and BVM-2 for baby corn were registered under moderately resistant category against MLB and BLSB diseases, while few of pop corn hybrids showed moderately susceptible reaction.